Acupuncture with manual and low frequency electrical stimulation as experienced by women with polycystic ovary syndrome: a qualitative study - Billhult Annika; Stener-Victorin Elisabet (BMC, 2012)
Abstract Background Polycystic ovary syndrome (PCOS) affects 5-10 percent of all fertile women and is associated with anovulation/oligoovulation, hyperandrogenism, and polycystic ovaries. Pharmacological treatment is often effective but associated with unwanted side effects. Acupuncture treatments have been shown to improve menstrual bleeding patterns and ovulation as well as hyperandrogenism, without side effects. The purpose of the present study was to describe the experience of acupuncture for women diagnosed with PCOS. Methods Eight women with PCOS living in western Sweden, were interviewed following repeated acupuncture treatments. Data was analyzed using systematic text condensation as described by Malterud. Results The experience of acupuncture for women diagnosed with PCOS can be described in five categories; the experience of hope, getting results, feelings of responsibility, skepticism and proof of effect, and feeling normal. Conclusion Since acupuncture is a promising treatment for the symptoms of the common syndrome PCOS, the present study adds to the knowledge base by providing the important experiences of patients receiving the treatment. Acupuncture provides a possibility for patients to gain hope as the treatment shows results. The results show that acupuncture empowers the patients to take responsibility for their future well-being, although they may have been initially skeptical to the treatment. Because the syndrome had affected them for some time, even small changes offered a chance for them to feel that their bodies were capable of normal function. Trial Registration The trial is registered at Clinical Trials.gov with Identifier number NCT00484705.